2022
DOI: 10.1016/j.ibneur.2021.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated seizures on spatial exploration and immediate early gene expression in the hippocampus and dentate gyrus

Abstract: Immediate early genes (IEGs) are coordinately activated in response to neuronal activity and can cause activation of secondary response genes that modulate synaptic plasticity and mediate long-lasting changes in behaviour. Excessive neuronal stimulation induced by epileptic seizures induce rapid and dramatic changes in IEG expression. Although the impact of acute seizure activity on IEG expression has been well studied, less is known about the long-term effects of chronic seizures on IEG induction during seizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
(80 reference statements)
2
4
0
Order By: Relevance
“…In the CNS, c-Fos, Egr1, and Arc are used as a markers of neuronal activity in the context of memory formation and development of multiple psychiatric disorders such as SZ and ASD ( Minatohara et al, 2016 ; Gallo et al, 2018 ). It was previously shown that multiple IEGs, including Egr1, Egr4, c-Fos, c-Jun, Naps4, Nur77, and Arc were upregulated in in vivo animal (from rodents to primates) and in in vitro models of epilepsy, as was confirmed in our study ( Kiessling and Gass, 1993 ; Barros et al, 2015 ; Kalinina et al, 2022 ; Rienecker et al, 2022 ). However, in contrast to earlier studies that used in situ hybridization, repetitive stimulations with PTZ, or using the earliest time-point at 30 min, we used more sensitive quantitative real-time PCR, which allowed us to detect upregulation of ten IEGs within a 9 ± 1 min period post-PTZ injections to ensure that all tested animals are alive.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the CNS, c-Fos, Egr1, and Arc are used as a markers of neuronal activity in the context of memory formation and development of multiple psychiatric disorders such as SZ and ASD ( Minatohara et al, 2016 ; Gallo et al, 2018 ). It was previously shown that multiple IEGs, including Egr1, Egr4, c-Fos, c-Jun, Naps4, Nur77, and Arc were upregulated in in vivo animal (from rodents to primates) and in in vitro models of epilepsy, as was confirmed in our study ( Kiessling and Gass, 1993 ; Barros et al, 2015 ; Kalinina et al, 2022 ; Rienecker et al, 2022 ). However, in contrast to earlier studies that used in situ hybridization, repetitive stimulations with PTZ, or using the earliest time-point at 30 min, we used more sensitive quantitative real-time PCR, which allowed us to detect upregulation of ten IEGs within a 9 ± 1 min period post-PTZ injections to ensure that all tested animals are alive.…”
Section: Discussionsupporting
confidence: 90%
“…It is well known that during epileptic seizures neuronal cells upregulate IEGs within minutes ( Kalinina et al, 2022 ). IEGs are responsible for many neuronal functions including their activation, long-term potentiation (LTP), memory, and CNS repair ( Kiessling and Gass, 1993 ; Dragunow, 1996 ; Gallo et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulation of npas4a, npas4b, erg1, fosab, and nr4a1 was seen in mutant wnt8b (Figure 4D.ii) fish and fosab, erg1, and npas4b in kcnd2 (Figure 4D.ii) mutants. All IEG expression was significantly downregulated, consistent with chronic epilepsy as opposed to the upregulation observed after acute seizure induction [24][25][26]. Models with no significant findings from LFP also showed no significant IEG DEGs (Figure 4C, D,E.ii).…”
Section: Transcriptomic Differences In Zebrafish Epilepsy Modelssupporting
confidence: 55%
“…Hippocampal and cortical hyperexcitability are the defining features of most epilepsies (Zhang et al., 2010 ), but the molecular mechanisms regulating excitability in these brain regions are not fully understood. Excessive neuronal stimulation induced by epileptic seizures results in rapid and dramatic changes in the expression of IEGs (Kalinina et al., 2022 ), which can mediate direct effects on neuronal excitability and function. Inhibition of IEG induction by antisense oligonucleotides can disrupt seizure development in several animal models of epilepsy (Chiasson et al., 1998 ; Panegyres & Hughes, 1997 ; Rocha & Kaufman, 1998 ; Rocha et al., 1999 ; Suzukawa et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%